The Need for an Alternative to Culling Day-Old Male Layer Chicks: A Survey on Awareness, Alternatives, and the Willingness to Pay for Alternatives in a Selected Population of Dutch Citizens - de Haas, Elske N.; Oliemans, Eva; van Gerwen, Maite A. A. M. (Frontiers in Veterinary Science, 2021)
A concerning by-product of producing laying hen chicks are the hatched male layer chicks. As a consequence of their inability to lay eggs these male chicks are culled as one day-old chicks in the hatchery. To find an alternative for this ethical dilemma, (generally) three alternatives are under study, namely: in-ovo gender determination; dual-purpose breeds; and the rearing of layer cockerels. In order to assess the awareness of this practice and preference for one of the alternatives we conducted an online-survey of the Dutch public. Most of the 259 respondents completing the survey were highly educated woman (HEW, n =143) and others (REST, n =86). The questionnaire was divided in six topics: 1. general knowledge of the poultry industry, 2. awareness of culling male layer chicks (CMC) and 3. its acceptability, 4. alternatives to CMC, 5. willingness to pay (WTP) for eggs without CMC, and 6. WTP for cockerel meat. Awareness about CMC was 52% and its acceptability was rejected by 78% (HEW) and 67% (REST). The level of acceptability increased when more salient facts were given, and all respondents agreed that an alternative was needed (90% (HEW), 84% (REST). For both groups of respondents more than 50% preferred in-ovo gender determination over keeping the current practice, or rearing dual-purpose breeds or male layers. Furthermore, the majority of respondents were WTP more than double the price for eggs without CMC being involved. Roughly 40% would not buy processed cockerel meat-burgers, most likely due to their vegan or vegetarian diet. Of the remaining respondents, half were WTP the current price or 1 euro more for processed cockerel meat-burgers. The most important factors when buying poultry meat or eggs without CMC were food safety, animal friendliness (welfare), and the environment; price was the least important factor. Despite the skewed respondents background, the results of our survey show that consumers are willing to pay more for poultry-products which do not require culling day-old male chicks.